Bronson [videorecording (DVD)] - Refn, Nicolas Winding, 1970-; Hardy, Tom, 1977-; King, Matt, 1968-; Lance, James, 1975-; Burton, Amanda, 1956- (Magnolia Home Entertainment, 2010)
Michael Peterson was 19 years old in 1974. Reckless, and hoping to make a name for himself, he picked up a homemade sawed-off shotgun and set off to rob a post office. Caught and arrested soon after, he was convicted and sentenced to seven years in prison. Ultimately, Peterson ended up behind bars for 34 years, 30 of which were spent in solitary confinement. While incarcerated, his alter ego, Charles Bronson, surfaced and eventually replaced his own personality.